Computer Security. ESORICS 2021 International Workshops: CyberICPS, SECPRE, ADIoT, SPOSE, CPS4CIP, and CDT&SECOMANE, Darmstadt, Germany, October 4-8, 2021, Revised Selected Papers - Katsikas, Sokratis; Lambrinoudakis, Costas; Cuppens, Nora; Mylopoulos, John; Kalloniatis, Christos; Meng, Weizhi; Furnell, Steven; Pallas, Frank; Pohle, Jörg; Sasse, M. Angela (Lecture Notes in Computer Science, 2022)
This book constitutes the refereed proceedings of six International Workshops that were held in conjunction with the 26th European Symposium on Research in Computer Security, ESORICS 2021, which took place during October 4-6, 2021. The conference was initially planned to take place in Darmstadt, Germany, but changed to an online event due to the COVID-19 pandemic.The 32 papers included in these proceedings stem from the following workshops:the 7th Workshop on the Security of Industrial Control Systems and of Cyber-Physical Systems, CyberICPS 2021, which accepted 7 papers from 16 submissions;the 5th International Workshop on Security and Privacy Requirements Engineering, SECPRE 2021, which accepted 5 papers from 8 submissions;the 4th International Workshop on Attacks and Defenses for Internet-of-Things, ADIoT 2021, which accepted 6 full and 1 short paper out of 15 submissions; the 3rd Workshop on Security, Privacy, Organizations, and Systems Engineering, SPOSE 2021, which accepted 5 full and 1 short paper out of 13 submissions.the 2nd Cyber-Physical Security for Critical Infrastructures Protection, CPS4CIP 2021, which accepted 3 full and 1 short paper out of 6 submissions; and  the 1st International Workshop on Cyber Defence Technologies and Secure Communications at the Network Edge, CDT & SECOMANE 2021, which accepted 3 papers out of 7 submissions.The following papers are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com:Why IT Security Needs Therapy by Uta Menges, Jonas Hielscher, Annalina Buckmann, Annette Kluge, M. Angela Sasse, and Imogen VerretTransferring Update Behavior from Smartphones to Smart Consumer Devices by Matthias Fassl, Michaela Neumayr, Oliver Schedler, and Katharina KrombholzOrganisational Contexts of Energy Cybersecurity by Tania Wallis, Greig Paul, and James IrvineSMILE - Smart eMaIl Link domain Extractor by Mattia Mossano, Benjamin Berens, Philip Heller, Christopher Beckmann, Lukas Aldag, Peter Mayer, and Melanie VolkamerA Semantic Model for Embracing Privacy as Contextual Integrity in the Internet of Things by Salatiel Ezennaya-Gomez, Claus Vielhauer, and Jana Dittmann Data Protection Impact Assessments in Practice - Experiences from Case Studies by Michael Friedewald, Ina Schiering, Nicholas Martin, and Dara Hallinan